2018
DOI: 10.1007/s00170-018-3092-5
|View full text |Cite
|
Sign up to set email alerts
|

Operations mechanism of postponement strategy for service-oriented manufacturing

Abstract: With the rapid growth of individualized customer demands, manufacturers are supposed to pay more attention to the interaction between service and product. In this context, the concept called service-oriented manufacturing (SOM) has been promoted. Postponement strategy, while has already been widely studied in manufacturing systems, still lacks being well understood about its operations mechanism for SOM. Therefore, the purpose of this paper is to provide a further insight into an operations mechanism in which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Until the 1990s, some high-tech enterprises and automobile manufacturing enterprises gradually pay attention to the theory of delay strategy and form a scale theoretical system.Budiman and Rau [4][5] proposed a two-stage stochastic model of supply chain network combined with delay strategy in order to solve the uncertain demand of the customers, and proposed a mixed-integer model of green supply chain network considering the delay strategy, and this model can reduce the cost under strict environmental policies.Phares and Jr [6] intervened in the supply chain uncertainty of a beer company and explored how the delay strategy can benefit the beer supply chain.Zheng, Shi and Wu [7] et al explored the supply chain of standard and customized products in a manufacturer and retailer system with two ordering opportunities under the delay strategy. Weskamp [8] et al proposed to hedge supply chain risk with delay strategy and constructed a two-stage stochastic mixed integer linear programming model to determine the decision considering lead time, penalty cost of shortages; Jabbarzadeh, Haughton, and Pourmehdi [9] proposed a two-objective robust optimization model to reduce the supply chain cost and reduce greenhouse gas emissions, which is used for integrated production and distribution planning in supply chains with delay strategies; Li, Wang and Cheng [10] developed an economic production quantity (EPQ)-based planned backordering model, which demonstrated that delay strategies can reduce the total average cost in some cases; Luo, Zhao and Song [11] pointed out the limitations and shortcomings of traditional delay strategies, and developed a model for service-oriented manufacturing environments. A delay strategy for service-oriented manufacturing environment was developed.…”
Section: Introductionmentioning
confidence: 99%
“…Until the 1990s, some high-tech enterprises and automobile manufacturing enterprises gradually pay attention to the theory of delay strategy and form a scale theoretical system.Budiman and Rau [4][5] proposed a two-stage stochastic model of supply chain network combined with delay strategy in order to solve the uncertain demand of the customers, and proposed a mixed-integer model of green supply chain network considering the delay strategy, and this model can reduce the cost under strict environmental policies.Phares and Jr [6] intervened in the supply chain uncertainty of a beer company and explored how the delay strategy can benefit the beer supply chain.Zheng, Shi and Wu [7] et al explored the supply chain of standard and customized products in a manufacturer and retailer system with two ordering opportunities under the delay strategy. Weskamp [8] et al proposed to hedge supply chain risk with delay strategy and constructed a two-stage stochastic mixed integer linear programming model to determine the decision considering lead time, penalty cost of shortages; Jabbarzadeh, Haughton, and Pourmehdi [9] proposed a two-objective robust optimization model to reduce the supply chain cost and reduce greenhouse gas emissions, which is used for integrated production and distribution planning in supply chains with delay strategies; Li, Wang and Cheng [10] developed an economic production quantity (EPQ)-based planned backordering model, which demonstrated that delay strategies can reduce the total average cost in some cases; Luo, Zhao and Song [11] pointed out the limitations and shortcomings of traditional delay strategies, and developed a model for service-oriented manufacturing environments. A delay strategy for service-oriented manufacturing environment was developed.…”
Section: Introductionmentioning
confidence: 99%